2007
DOI: 10.1016/s0929-6646(09)60294-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Results in Rotator Cuff Tears with Shoulder Stiffness

Abstract: A combined procedure of manipulation, lysis of adhesions, acromioplasty and repair of rotator cuff is a satisfactory procedure for patients with rotator cuff tears and associated shoulder stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 26 publications
1
47
2
Order By: Relevance
“…Preoperative shoulder stiffness in patients who undergo rotator cuff repair is common, with a reported prevalence of 12.3% to 41.7%. 1,4,8,[18][19][20] However, the definition of shoulder stiffness is one of the controversial points, and authors have used different definitions. 16 Furthermore, the incidence and magnitude of the problem, as well as the treatment protocol, have not been thoroughly studied.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative shoulder stiffness in patients who undergo rotator cuff repair is common, with a reported prevalence of 12.3% to 41.7%. 1,4,8,[18][19][20] However, the definition of shoulder stiffness is one of the controversial points, and authors have used different definitions. 16 Furthermore, the incidence and magnitude of the problem, as well as the treatment protocol, have not been thoroughly studied.…”
Section: Discussionmentioning
confidence: 99%
“…28 Because of the clinical importance of postoperative shoulder stiffness, several authors have made an effort to develop criteria for defining shoulder stiffness. 8,10,[29][30][31] Huberty et al 30 defined stiffness as patient dissatisfaction, and patients who judged as having a disabling lack of shoulder motion were regarded as having a stiff shoulder. On the basis of this definition, Huberty et al found that 24 of 489 patients (4.9%) developed postoperative shoulder stiffness after rotator cuff repair at a mean of 8 months.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed early functional recovery and found shoulder stiffness may be a preoperative factor influencing the functional recovery period. Hsu et al [14] reported patients with partial tears of the rotator cuff had better clinical scores than those with complete tears. However, morphologic features of the rotator cuff tear did not influence functional recovery time in our study.…”
Section: Discussionmentioning
confidence: 99%